Greater Kansas City and the urban crisis, 1830-1968 - Hutchison, Van William (Kansas State University, 2013)
In the last two decades, the study of postwar American cities has gone through a significant revisionist reinterpretation that overturned an older story of urban decay and decline beginning with the tumultuous 1960s and the notion that a conservative white suburban backlash politics against civil rights and liberalism appeared only after 1966. These new studies have shown that, in fact, American cities had been in jeopardy as far back as the 1940s and that white right-wing backlash against civil rights was also much older than previously thought. This “urban crisis” scholarship also directly rebutted neoconservative and New Right arguments that Great Society liberal programs were at fault for the decline of inner-city African American neighborhoods in the past few decades by showing that the private sector real estate industry and 1930s New Deal housing programs, influenced by biased industry guidelines, caused those conditions through redlining. My case study similarly recasts the history of American inner cities in the last half of the twentieth century. It uses the Greater Kansas City metropolitan area, especially Kansas City, Missouri and Kansas City, Kansas, as a case study. I deliberately chose Kansas City because traditional urban histories and labor histories have tended to ignore it in favor of cities further east or on the west coast. Furthermore, I concur with recent trends in the historical scholarship of the Civil Rights Movement towards more of a focus on northern racism and loczating the beginning of the movement in the early twentieth century. In this study, I found evidence of civil rights activism in Kansas City, Missouri as far back as the late 1860s and 1870s. I trace the metropolitan area’s history all the way back to its antebellum beginnings, when slavery still divided the nation and a national railroad system was being built. I weave both labor and changes in transportation over time into the story of the city and its African-American population over time.
Keywords: Kansas City; Urban crisis; African American history; Transportation; Labor history; History (0578)